Surviving the Urban Jungle: Anthropogenic Threats, Wildlife-Conflicts, and Management Recommendations for African Crowned Eagles - McPherson, Shane C.; Sumasgutner, Petra; Hoffman, Ben H.; Padbury, Bruce D. L.; Brown, Mark; Caine, Tammy P.; Downs, Colleen T. (Frontiers in Ecology and Evolution, 2021)
Larger carnivores often trigger human-wildlife conflicts that arise from perceived threats to humans and domestic animals' safety, which generate the need for management and removal strategies. These issues become especially challenging when humans and wildlife coexist close to one another, for example, in urban landscapes. African Crowned Eagles (Stephanoaetus coronatus) are powerful forest raptors that breed within the metropolitan green-space system of Durban and Pietermaritzburg, South Africa. Negative human-wildlife interactions can occur because eagles occasionally predate on pets, and provisioning domestic stock to nest sites has previously been quantified. Here, wildlife management becomes critical, usually aimed at reducing or eliminating causes of economic or social harm, but have to be balanced against conservation goals regarding threatened species. In this study, we (i) identified causes of harm or loss of Crowned Eagles because of injuries (n = 53 incidents; 31 mortalities); and (ii) describe interactions with negative perceptions to human livelihoods, particularly concerning predation on pets and livestock. Anthropogenic causes of mortality were more likely to be reported than remote natural deaths, which provides important opportunities for mitigation measures. Most avoidable are electrocution on utility poles, persecution via gunshot wounds and poisoning (targeted or secondary), while collisions with anthropogenic structures, such as glass panes, vehicles and fence wires, are more challenging to mitigate. Of 44 verified Crowned Eagle versus pets and livestock conflicts, we documented 19 dog attacks (2012 – 2020), with detrimental impacts on social perception and acceptance of urban eagles. Pet and livestock conflicts were primarily associated with juveniles and immature eagles (83%). Of these, 19% occurred during September alone, which marks the end of the post-fledging dependency period; 70% occurred outside the breeding season. We provide management recommendations regarding various categories of Crowned Eagle human-wildlife interactions. For example, activities such as rehabilitation and falconry can coordinate to achieve a high standard of public support and conservation outcomes for Crowned Eagles. Finally, we discuss different management intervention strategies, including rehabilitation, falconry, re-wildling processes, and lethal control of specific ‘problem’ individuals towards achieving the goal of sustainable, healthy Crowned Eagle populations that coexist with humans in urban landscapes.